ANALYSIS OF THE EFFECT OF TAXPAYER AWARENESS LEVEL OF TAXPAYER COMPLIANCE IN PAYING THE PROPERTY TAX IN PAKISJAYA, WEST JAVA, INDONESIA - Purwandari, Dian; Marlian, Sari; Mulyati, Yati (International Journal of Psychosocial Rehabilitation, 2020)
Tax has an important role in the Indonesian economy because it is one of the sources of state revenue used to finance state expenditure. Therefore, it is important for the Indonesian government to increase state revenue through the tax sector, including through increasing taxpayer compliance in paying taxes. However, at present the tax compliance in paying the Property Tax is still lacking. The purpose of this study was to determine the effect of the level of awareness of taxpayer compliance in paying Property Tax in Pakisjaya, Karawang Regency. The method in this study is a quantitative method with descriptive and verification research approaches. The population in this study are all individual taxpayers of Property tax in the Pakisjaya, Karawang regency and 100 taxpayers were set as a sample. Data analysis methods used are the classic assumption test, multiple regression analysis, coefficient of determination and hypothesis test. The type of data is primary data. The results showed that the level of awareness affected the compliance of taxpayers in paying the Property Tax in the District of Pakisjaya, Karawang Regency, significantly influence both partially and simultaneously. Thus, the government should make efforts to increase taxpayer awareness in paying Property taxes by intensifying socialization, counseling, as well as providing knowledge and understanding related to taxpayer awareness in paying Property taxes.